Routledge Handbook of African Literature - Adejunmobi, Moradewun; Coetzee, Carli (Taylor & Francis, 2019)
The turn of the twenty-first century has witnessed an expansion of critical approaches to African literature. The Routledge Handbook of African Literature is a one-stop publication bringing together studies of African literary texts that embody an array of newer approaches applied to a wide range of works. This includes frameworks derived from food studies, utopian studies, network theory, eco-criticism, and examinations of the human/animal interface alongside more familiar discussions of postcolonial politics. The handbook is divided into seven parts, i) Mapping political agencies ii) Journeys, geographies, identities iii) Working through genre iv) The world of and beyond humans v) Everyday sociality vi) Bodies, subjectivities, affect vii) Literary networks. In each, contributors address the themes of the section from a variety of perspectives in conjunction with analysis of different literary texts. Every chapter is an original research essay written by a broad spectrum of scholars with expertise in the subject, providing an application of the most recent insights into analysis of particular topics or application of particular critical frameworks to one or more African literary works. The handbook will be a valuable interdisciplinary resource for scholars and students of African literature, African culture, postcolonial literature and literary analysis.